Latent profiles of psychological capital in clinical nursing teachers and their association with the practice environment of nursing and perceived social support - He, Yunling; Wang, Dongxue; Wang, Lining; Liao, Rong (Frontiers in Psychology, 2025)
BackgroundClinical nursing teachers (CNTs) play a critical role in nursing education, and their psychological capital (PsyCap) acts as an intrinsic motivational resource to assist them in facing the challenges of clinical teaching.PurposeThis research aims to examine the diversity of PsyCap in CNTs and its associated influencing factors via latent profile analysis.MethodsA cross-sectional study of 322 CNTs was conducted using four scales, following the STROBE statement guidelines.ResultsThe levels of PsyCap among CNTs could be categorized as low (24.1%), moderate (53.6%), and high (22.3%) PsyCap. Moreover, with the multiple logistic regression analysis, there are significant effects of the length of nursing experience, fertility status, self-reported health, nursing practice environment, and social support on the different categories of the PsyCap of CNTs (p < 0.05).ConclusionThe majority of the PsyCap of CNTs was at the moderate level, with obvious classification characteristics, which are influenced by multiple sociodemographic factors, e.g., length of nursing experience, fertility status, self-reported health, practice environment of nursing, and perceived social support.